Both Subunits of ATP-Citrate Lyase from Chlorobium tepidum Contribute to Catalytic Activity - Kim, Wonduck (American Society for Microbiology, 2006)
ATP-citrate lyase (ACL) is an essential enzyme of the reductive tricarboxylic acid (RTCA) pathway of CO(2) assimilation. The RTCA pathway occurs in several groups of autotrophic prokaryotes, including the green sulfur bacteria. ACL catalyzes the coenzyme A (CoA)-dependent and MgATP-dependent cleavage of citrate into oxaloacetate and acetyl-CoA, representing a key step in the RTCA pathway. To characterize this enzyme from the green sulfur bacterium Chlorobium tepidum and determine the role of its two distinct polypeptide chains, recombinant holo-ACL as well as its two individual subunit polypeptides were synthesized in Escherichia coli. The recombinant holoenzyme, prepared from coexpressed large and small ACL genes, and the individual large and small subunit polypeptides, prepared from singly expressed genes, were all purified to homogeneity to high yield. Purified recombinant holo-ACL was isolated at high specific activity, and its k(cat) was comparable to that of previously prepared native C. tepidum ACL. Moreover, the purified recombinant large and small subunit polypeptides were able to reconstitute the holo-ACL in vitro, with activity levels approaching that of recombinant holo-ACL prepared from coexpressed genes. Stoichiometric amounts of each subunit protein were required to maximize the activity and form the most stable structure of reconstituted holo-ACL. These results suggested that this reconstitution system could be used to discern the catalytic role of specific amino acid residues on each subunit. Reconstitution and mutagenesis studies together indicated that residues of each subunit contributed to different aspects of the catalytic mechanism, suggesting that both subunit proteins contribute to the active site of C. tepidum ACL.